Biology and Management of Thickhead (Crassocephalum crepidioides) in Ornamental Crop Production - Allison Bechtloff; Shawn T. Steed; Nathan S. Boyd; Stephen Christoper Marble (EDIS)
Typically found in shadehouses and shaded areas of nursery production, thickhead grows aggressively in containers and can outcompete nursery crops for water, nutrients, and light. This erect, sparingly branched, herbaceous annual, grows up to 4 feet tall and germinates over a wide range of pH, salt, and temperature conditions. This four-page fact sheet describes thickhead (Crassocephalum crepidioides) and various methods for its control in ornamental crop production. Written by Allison Bechtloff, Shawn Steed, Chris Marble, and Nathan Boyd and published by the Environmental Horticulture Department.http://edis.ifas.ufl.edu/ep534